Analysis of volatile flavour compounds and acrylamide in roasted Malaysian tropical almond (Terminalia catappa) nuts using supercritical fluid extraction. - Olusegun, Lasekan; Abbas, Kassim Ali (Elsevier, 2010)
Considering the importance of tropical almond nuts as a snack item, a study was conducted to identify the flavour volatiles and acrylamide generated during the roasting of the nuts. The supercritical fluid extracted flavour components revealed 74 aroma active compounds made up of 27 hydrocarbons, 12 aldehydes, 11 ketones, 7 acids, 4 esters, 3 alcohols, 5 furan derivatives a pyrazine, and 2 unknown compounds. While low levels of acrylamide (8-86 microg/kg) were obtained in the roasted nuts, significant (P<0.05) increases occurred in concentration with increased roasting temperature and time. Carboxylic acids were the most abundant volatiles in the roasted almond nuts and less significant (P>0.05) concentration of acrylamide was generated with mild roasting and shorter roasting period.